Evaluation of natural compounds as folate biosynthesis inhibitors in Mycobacterium leprae using docking, ADMET analysis, and molecular dynamics simulation - Alanzi Abdullah R.; Alharbi Hattan A. (Open Chemistry)
Mycobacterium leprae, the bacterium that causes leprosy, is still a public health concern which requires innovative strategies to fight drug-resistant forms. This study investigates the potential of natural compounds as FolP protein inhibitors, a key enzyme in the folate biosynthesis pathway critical for M. leprae survival. The aim of this work was to search for natural chemicals that can inhibit FolP protein using molecular docking and absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis. Using the standard precision method of the Glide tool, the FolP protein was matched to a library of natural products comprising 1,400 compounds. Ten of the most promising compounds were chosen for further investigation based on their binding affinities. The binding affinities of the selected compounds ranged from −7.851 to −7.219 kcal/mol. The ADMET properties and toxicity risks of the selected compounds were assessed, and the predicted values of three compounds (LTS0262854, LTS0241035, and LTS0033598) were found to be within an acceptable range. Moreover, the docking studies were supported by molecular dynamics (MD) simulation. MD simulations showed that these compounds were stable as potent inhibitors inside the protein binding region. The findings of this study may help develop safe and efficient antileprosy medications, addressing the urgent demand for advanced leprosy care and treatment.